Mercury Pictures presents : a novel - Marra, Anthony (Hogarth, 2022)
"When we first meet Maria Lagana, she's rewriting scripts at Mercury Pictures, a failing Hollywood studio known for its schlock. Maria's job is to re-craft dialogue and action to circumvent the censors, a skill she's mysteriously adept at. Born in Italy, as a teenager Maria witnessed Mussolini's censors arrest her father, an event that will destroy her family and burden Maria with questions of guilt and responsibility she will carry with her throughout this wondrous, far-reaching novel. Like many before her, Maria has come to Hollywood to outrun her past. Despite its cheap production values and factory-approach to making movies, Mercury Pictures is a nexus of refugees and emigres, each struggling to reinvent themselves in the land of celluloid. There's Artie, the studio boss, a man of many toupees who barely escaped the pogroms of Eastern Europe; there's Anna, a set designer, who ran afoul of Hitler; and there's Eddie Lu, a struggling actor and Maria's boyfriend, who despite being born in Los Angeles encounters the worst of America's xenophobia. After the attack on Pearl Harbor, everything changes for Maria and her world, forcing her come to terms with her father's fate--and her own"--